Consequences of the one-electron reduction and photoexcitation of unsymmetric bis-imidazolium salts: dedicated to Professor Gottfried Huttner - Gierz, Verena; Deißler, Christine; Rominger, Frank (Chemistry - a European journal, 2012)
Coupling of uronium salts with in situ generated N-heterocyclic carbenes provides straightforward access to symmetrical [4]2+ and unsymmetrical bis-imidazolium salts [6]2+ and [9]2+. As indicated by cyclic and square-wave voltammetry, [6]2+ and [9]2+ can be (irreversibly) reduced by one electron. The initially formed radicals [6].+ and [9].+ undergo further reactions, which were probed by EPR spectroscopy and density functional calculations. The final products of the two-electron reduction are the two carbenes. Upon irradiation with UV light both [6]2+ and [9]2+ emit at room temperature in solution but with dramatically different characteristics. The different fluorescence behavior is analyzed by emission spectroscopy and interpreted by using time-dependent density functional calculations as largely due to different excited-state dynamics of [6]2+ and [9]2+. The geometries of both radicals [6].+ and [9].+ and excited states [6]2+* and [9]2+* are substantially different from those of the parent ground-state molecules.